External Morphogenesis of Heart in Pre-natal Non-descript Sheep (Ovis aries) - Sahu, S.K.; Mishra, U.K.; Sathapathy, S.; Panda, S.K.; Nath, I.; Joshi, S. K. (Indian Journal of Veterinary Anatomy, 2023)
The external gross morphogenesis of heart was recorded in sheep foeti divided into three age groups, i.e. early prenatal (up to 50 days), mid prenatal (51-100 days) and late prenatal (101 to 150 days) having four animals in each group. The shape of the heart was triangular in 33 and 38 days of gestation, tubular in 72 days of gestation and became conical in 59 days, 96 days, 105 days, 120 days and 149 days of gestation.The convexity of the cranial border of the heart increased with advancement of age, whereas the caudal border remained straight in all the age groups. The coronary grooves appeared as faint line in foeti of 38 days of gestation, apparently distinct in foeti aged 59 days to 96 days of gestation and quite prominent in 105 days to 149 days foeti. The longitudinal groves appeared as narrow lines in foeti aged 43 days and 49 days, as broad lines in foeti aged 59 days and 96 days, shallow depression in foeti aged 105 days and deep depression in foeti aged 120 days and onwards. The right and left auricles were half-moon shaped in sheep foeti from 59 days to 96 days of gestation. The ventricle was triangular in shape in 33 days to 96 days foeti and became elongated and conical in 105 days to149 days foeti. The outline ofbase of the heart was oval in 33 days to 96 days foeti that became elliptical in 105 days to 149 days foeti. The apex of the heart was pointed in 33 days of gestation, blunt in 38 days of gestation and conical in shape in 43 days to149 days of gestation. The present study provided a detailed baseline data on the age wise external morphological development of heart in prenatal non-descript sheep of Odisha that can be utilised for studying various congenital anomalies in different breeds of sheep and comparisons can be made with other domestic animals.